A Short Course on Development in “Post-conflict” Congo - Podur, Justin (Radical Teacher, 2014)
<!– P margin-bottom: 0.21cm; direction: ltr; color: rgb(0, 0, 0); P.western font-family: "Times New Roman",serif; font-size: 12pt; P.cjk font-family: "DejaVu Sans","Times New Roman"; font-size: 12pt; P.ctl font-family: "Lohit Hindi","Times New Roman"; font-size: 12pt; A.western:link A.ctl:link –> It was during my brief teaching in Bukavu, in the east of the Democratic Republic of Congo (DRC), that I came to understand the power of neoliberalism in shaping the narrative of DRC’s past, present, and future. While my students argued that the DRC’s problems stemmed from local corruption, not ongoing colonialism, I was trying to present a more diverse story of development, one that cracks in the neoliberal narrative and lets democracy and the public sector play a role.